Role of Membrane Lipid Rafts in MRP4 (ABCC4) Dependent Regulation of the cAMP Pathway in Blood Platelets - Belleville-Rolland, Tiphaine; Leuci, Alexandre; Mansour, Alexandre; Decouture, Benoit; Martin, Fanny; Poirault-Chassac, Sonia; Rouaud, Margot; Guerineau, Hippolyte; Dizier, Blandine; Pidard, Dominique; Gaussem, Pascale; Bachelot-Loza, Christilla (Thrombosis and Haemostasis, 2021)
Background Platelet cytosolic cyclic adenosine monophosphate (cAMP) levels are balanced by synthesis, degradation, and efflux. Efflux can occur via multidrug resistant protein-4 (MRP4; ABCC4) present on dense granule and/or plasma membranes. As lipid rafts have been shown to interfere on cAMP homeostasis, we evaluated the relationships between the distribution and activity of MRP4 in lipid rafts and cAMP efflux.Methods Platelet activation and cAMP homeostasis were analyzed in human and wild-type or MRP4-deleted mouse platelets in the presence of methyl-β-cyclodextrin (MßCD) to disrupt lipid rafts, and of activators of the cAMP signalling pathways. Human platelet MRP4 and effector proteins of the cAMP pathway were analyzed by immunoblots in lipid rafts isolated by differential centrifugation.Results MßCD dose dependently inhibited human and mouse platelet aggregation without affecting per se cAMP levels. An additive inhibitory effect existed between the adenylate cyclase (AC) activator forskolin and MßCD that was accompanied by an overincrease of cAMP, and which was significantly enhanced upon MRP4 deletion. Finally, an efflux of cAMP out of resting platelets incubated with prostaglandin E1 (PGE1) was observed that was partly dependent on MRP4. Lipid rafts contained a small fraction (≈15%) of MRP4 and most of the inhibitory G-protein Gi, whereas Gs protein, AC3, and phosphodiesterases PDE2 and PDE3A were all present as only trace amounts.Conclusion Our results are in favour of part of MRP4 present at the platelet surface, including in lipid rafts. Lipid raft integrity is necessary for cAMP signalling regulation, although MRP4 and most players of cAMP homeostasis are essentially located outside rafts.
Keywords: platelets; MRP4 (ABCC4); cAMP; lipid rafts; microdomains